2015
DOI: 10.1097/ncc.0000000000000122
|View full text |Cite
|
Sign up to set email alerts
|

Self-management for Adult Patients With Cancer

Abstract: Guiding patients with cancer in self-care management is important for overall functional status and quality of life. Further investigation and tailored interventions are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 67 publications
4
64
0
1
Order By: Relevance
“…Similar to previous reviews, we found substantial variability in all aspects of the interventions. This variability may hamper replication, scale‐up, and integration into practice.…”
Section: Discussionsupporting
confidence: 87%
“…Similar to previous reviews, we found substantial variability in all aspects of the interventions. This variability may hamper replication, scale‐up, and integration into practice.…”
Section: Discussionsupporting
confidence: 87%
“…The self-care advice directly related to the reported concerns was another important asset that could enable the patients to take an active part. Guiding patients with cancer in self-care management is essential for functional status and HRQoL [35]. In our previous study, we found that strategies for self-care management for patients with prostate cancer are rare in the literature, and in interviews with patients, they expressed scarce experience of support or information about self-care activities during treatment [5].…”
Section: Discussionmentioning
confidence: 99%
“…Outpatients, who are by definition outside the hospital setting, must employ a number of self-management strategies to cope with their cancer symptoms and treatment. When these coping strategies fail, the patients’ unmet needs may require prompt access to care professionals [48]. A possible explanation of the association between high ITW intensity and positive perception of Prompt access to care is that ITW is aimed at improving care coordination by facilitating appropriate referral mechanisms to the relevant team member [49].…”
Section: Discussionmentioning
confidence: 99%